Fungi growth on rattan board exposed to natural weathering - Tajuddin, Maisarah; Ahmad , Zuraida; Sulaiman, Mohd Faris Haikal; Halim, Zahurin; Maleque, Md. Abdul (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The objective of this study was to investigate the fungi growth on fabricated rattan board under 12 weeks’ exposure in natural weathering. The rattan powder was pressed using a hot-press machine to be turned into rattan boards and they were placed on a 45oC inclined rack at an open area. Longer exposure time resulted in occurrences of more surface cracks, fungi growth, and eroded surfaces, which caused a deterioration of 68% in board weight. In addition, optimum temperature, high moisture content, and sufficient oxygen supply proved to be favorable conditions for fungi growth. The soft-rot fungi nourished the components of cell walls, as observed from the morphology analysis through SEM. In conclusion, fungi growth on rattan boards caused surface cracks, fibers collapse, disintegration into small parts, and finally, damaged the fabricated boards.